Leptospira as an emerging pathogen: a review of its biology, pathogenesis and host immune responses. (September 2010) - Evangelista, Karen V; Coburn, Jenifer
Leptospirosis, the most widespread zoonosis in the world, is an emerging public health problem, particularly in large urban centers of developing countries. Several pathogenic species of the genus Leptospira can cause a wide range of clinical manifestations, from a mild, flu-like illness to a severe disease form characterized by multiorgan system complications leading to death. However, the mechanisms of pathogenesis of Leptospira are largely unknown. This article will address the animal models of acute and chronic leptospire infections, and the recent developments in the genetic manipulation of the bacteria, which facilitate the identification of virulence factors involved in pathogenesis and the assessment of their potential values in the control and prevention of leptospirosis.